Peran Pendidikan Islam dalam Membentuk Nilai Moral Remaja di SMP Budi Luhur Mandiri Sangatta Utara - Ramdhani, Ratna Dwi; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
Islamic education greatly influences the morals and character of teenagers, especially through the spread of religious values ​​that are applied in everyday life. The focus of this research is to see the role of Islamic education as an agent of socialization in forming moral values ​​among teenagers and how teenagers view the role of Islamic education in forming their moral values ​​at Budi Luhur Mandiri Sangatta Utara Middle School. The aim of the research is to see the role of Islamic education as an agent of socialization in forming moral values ​​among teenagers, and to find out teenagers' views on the role of Islamic education in shaping their moral values ​​at Budi Luhur Mandiri Sangatta Utara Middle School. This research uses qualitative methods with a descriptive type. To collect data, researchers used interviews, observation and documentation. The research results show that spiritual and religious programs such as